Pengaruh Labelisasi Halal Terhadap Keputusan Pembelian Produk Makanan Kemasan Impor Pada Mahasiswa Fakultas Ekonomi Universitas Negeri Surabaya. - Yunitasari, Vivi; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2019)
This study aims to determine the effect of halal labeling on imported food products on consumer purchasing decisions. This research was conducted using quantitative research. The sample used in this study was 200 respondents taken from Economics Faculty students who had consumed and purchased imported food products in packaging using accidental sampling. Paying attention to the use of labels on products, this is very helpful because consumers will pay attention to the halal labels, composition, and nutritional tables before consumers make purchasing decisions, especially on imported packaged foods